Identifying the acoustic features in tonal phonemes in Chinese - Zajdler, Ewa (Glottodidactica, 2015)
The current paper refers to the particular phonetic and phonological substance of the Chinese language. The key topics include the acoustic features of tonal languages, speech sound and audio-perception, as well as some issues of acquisition of Chinese language skills and reception conditions. The difficulties in tonal phonemes identification in hearing-impaired native Chinese and in non-tonal language users learning Chinese as a foreign language inspire the scientists to research the register of tones, acoustic features of tonal languages, the fundamental frequency (F0), tone contour and duration, and the speech signal – natural and subjected to filtration.